Workplace Adaptation for Vocational Schools Graduates - Afrizal, Afrizal; Ana, Ana; Muktiarni, Muktiarni (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2021)
The essence and types of workplace adaptation as a choice of professional activities performed by vocational high school graduates are more closely related to the school learning system and employability skills. Researchers conducted a systematic literature review to investigate various sources of information on vocational high school graduates' workplace adaptation. A high degree of initial knowledge and skills, an interest in new organizations and professions, and, in the long run, possessing the appropriate character qualities and psychological qualities impact the effectiveness of workplace adaptation. The success of workplace adaptation is determined by a high level of initial knowledge and skills, an interest in new organizations and jobs, and, in the future, having the necessary character traits and psychological characteristics. Timely assistance from colleagues, supervisors, and managers, as well as the ability to anticipate difficulties and respond to situations promptly. The adaptation of the workplace for vocational high school graduates is strongly intertwined with the implementation of the stages and roles of student vocational career guidance. The authors focus on the creation of a framework that vocational high school graduates can use to prepare them for the workplace, beginning with the preparation, search, evaluation, negotiation, and ending with starting and improving jobs as a source of income. This framework is strengthened by increasing skills, specifically soft skills as the fundamental skills required by job seekers.